Potential predictors for progression of moyamoya disease: A systematic review and meta-analysis - Cao, Jun; Xing, Zixuan; Dai, Ling; Wang, Tao; Zhang, Yuhai; Feng, Yao; Chen, Yanfei (Frontiers in Neurology, 2023)
Background The progress of Moyamoya disease (MMD) is often accompanied by the occurrence of new ischemia or hemorrhagic events, which was difficult to predict. This systematic review and meta-analysis aimed to identify predictors for progression in MMD patients. Methods We searched PubMed, Web of Science, Cochrane Library, and Embase databases up to December 10th, 2022 for randomized controlled trials, case-control studies, or cohort studies reporting predictors of disease progression in MMD patients. The results of each predictor were pooled by meta-analysis and further analyzed by subgroup analysis for predictors of unilateral to bilateral progression of MMD. Results A total of 842 patients from 12 studies were included. The estimated pooled means indicated lower age (standard mean difference [SMD]: −0.29, 95% confidence interval [CI]: −0.55 to −0.03; P = 0.03), family history (odds ratio [OR] 3.97, 95% CI: 1.96 to 8.03; P < 0.001) and contralateral abnormality (OR 3.95, 95% CI: 1.10 to 14.20; P = 0.04) were associated with progression in MMD patients. Subgroup analyses indicated that the same three factors were associated with the progression of unilateral to bilateral MMD. Conclusions This meta-analysis revealed that lower age, family history and contralateral abnormality were associated with progression in MMD patients. The same three factors are associated with the progression of unilateral to bilateral MMD. Further studies are needed to validate our results.